Urban entrepreneurialism in fifa World Cup host cities: the case of Porto Alegre - de Oliveira, Clarice Misoczky; Misoczky, Maria Ceci (Organizações & Sociedade, 2016)
The aim of the study that gave rise to this paper was to analyse the practices in place in Porto Alegre in relation to Large Urban Projects (LUPs) linked to the 2014 FIFA World Cup. An instrumental case study was performed, incorporating three units of analysis: mobility, stadiums and the waterfront, comprising 18 projects. Following the introduction, a resentation on the methodological procedures and two theoretical sections are given: on the concepts of urban entrepreneurialism and urban marketing, and on definitions and practices of planning and their expression in cities. The case of Porto Alegre then follows. Lastly, is an analysis indicating how each project is connected to urban entrepreneurial strategies. It concludes, indicating that the fact of being a host city was used to disseminate the image of a modern, developed and efficient city; the choice and management of projects was interconnected to economic growth, entrepreneurialism and the creation of an environment favourable for business; and the selection of LUPs led to a fragmented treatment of the territory. Under the aegis of speculation, urban planning lost relevance and the public administration renounced its position as market regulator.